SnapAssist v4 apps - Lye, Cheng Yin (Nanyang Technological University, 2024)
This project SnapAssist aims to revolutionise the field of photography by integrating technology into conventional photographic methods. By integrating actuators into an arduino-based system, SnapAssist enhances the capabilities of the pre-existing SnapAssist, it provides photographers and users with tools to achieve a broader range of creative outcomes. SnapAssist explores four different setups : a vibration motor-driven setup for dynamic motion effects, a stereo Bluetooth amplifier setup for audio visual synchronisation, solenoid-controlled air valve and a dual vibration motor setup for adjustable intensity control. Each setup is designed to broaden the scope of photography, enabling users to take precise, imaginative and high-quality photos. The focus of the project is on optimising the hardware and software components in order to ensure seamless integration and stability for practical use. The goal is to achieve a robust system that allows for users to explore different use cases in their craft by pushing the boundaries with technology enhanced photography.